Mismatch Negativity as an Indicator of Cognitive Sub-Domain Dysfunction in Amyotrophic Lateral Sclerosis - Iyer, Parameswaran Mahadeva; Mohr, Kieran; Broderick, Michael; Gavin, Brighid; Burke, Tom; Bede, Peter; Pinto-Grau, Marta; Pender, Niall P.; McLaughlin, Russell; Vajda, Alice; Heverin, Mark; Lalor, Edmund C.; et al. (Frontiers in Neurology, 2017)
Objective: To evaluate the utility of Mismatch Negativity (MMN), a neurophysiologic marker of non-motor cognitive processing, in amyotrophic lateral sclerosis (ALS). Methods: 89 patients, stratified into 4 different phenotypic presentations of Amyotrophic Lateral Sclerosis (67 spinal-onset, 15 bulbar-onset, 7 ALS-FTD, 7 C9ORF72 gene careers), and 19 matched controls underwent 128-channel EEG data recording. Subjects were presented with standard auditory tones interleaved with pitch-deviant tones in 3 recording blocks. The MMN response was quantified by peak amplitude, peak delay, average amplitude and average delay, 100-300ms after stimuli. 64 patients underwent cognitive screening using the Edinburgh Cognitive and Behavioural ALS Screen (ECAS), and 38 participants underwent contemporaneous cognitive assessment using the Stroop Colour Word Interference Test, which measures attention shift, inhibitory control and error monitoring. Results: The MMN response was observed in frontal and fronto-central regions of patient and control groups. Compared to controls, waveforms were attenuated in early onset and the average delay was significantly increased in all of the ALS subgroups, with no significant difference between sub-groups. Comparing with the control response, the ALS MMN response clustered into 4 new subgroups characterized by differences in response latency. The increased average delay correlated with changes in the Stroop Colour Word Interference Test; however, it did not show a direct relationship with age, gender, traditional phenotypes, Revised ALS Functional Rating Scale (ALSFRS-R), or ECAS scores. Conclusions & Significance: The MMN response in ALS patients reflects the cognitive dysfunction in specific sub-domains, as the new patient subgroups, identified by cluster analysis, do not segregate with existing clinical or cognitive classifications. Event-related potentials can provide additional quantitative neurophysiologic measures of impairment in specific cognitive sub-domains from which it may be possible to generate novel biologically-relevant subgroups of Amyotrophic Lateral Sclerosis. Keywords: ALS, Auditory mismatch Negativity (MMN), Neuronal networks, EEG, cognition, phenotyping